Exploring markets: Diamonds - Daniel Weber (IU Internationale Hochschule, 2024)
Exploring Markets is a paper series discussing niche markets with interesting characteristics. The paper on hand focuses on the market for diamonds. The paper discusses specific characteristics of supply and demand such as the supply chain from mining to retail, the dismantling of the diamond cartel, qualities of diamonds, the Kimberley Process Certification as an approach to ensure ethical sourcing, the role of advertisement in creating demand and the potential disruption of the diamond industry through labgrown diamonds.
Keywords: Z19; 650; Market Study; Diamonds